Strategi Perencanaan Keuangan untuk Mendorong Pertumbuhan UMKM Kos Purnomo - Wau, Novrianti; Yuliamir, Henry (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the financial strategy and business management of Kos Purnomo in facing the challenges of financial management and business development in the boarding house sector. Kos Purnomo is a small-scale boarding house business located in the strategic area of Bawen. The majority of tenants are students and young workers, so this market segment is very sensitive to price and service quality.  The focus of the research includes financial recording systems, cash flow management, investment strategies, and the level of resident satisfaction with the available facilities. This study uses a qualitative approach, with data collection through in-depth interviews with boarding house owners and residents, as well as direct observation of financial management practices.  The results showed that 60% of residents experienced late rent payments in the last three months, which resulted in irregular cash flow. Emergency maintenance costs, such as repairs to water installations and bathroom facilities, also add to the burden of expenses. For this reason, it is recommended to implement an automatic payment reminder system and allocate a reserve fund of at least 10% of monthly income.  In terms of investment, development plans such as adding rooms and improving Wi-Fi quality are hampered by limited capital. Alternative funding through cooperatives, small business loans, or strategic partnerships are recommended solution. The study also found that marketing strategies that rely solely on word of mouth are less effective. Social media-based approaches and digital promotions have been shown to increase the number of interested parties by up to 20% compared to conventional methods. Furthermore, residents' preferences in choosing boarding houses are influenced by affordable prices, locations close to activity centers, and the availability of supporting facilities such as Wi-Fi and private bathrooms. The provision of additional services such as laundry and catering is seen as an opportunity to increase resident satisfaction and strengthen competitiveness. Overall, the proposed strategies are expected to improve the sustainability of Kos Purnomo's business in the long term through financial efficiency, service differentiation, and digital marketing optimization.